Cardiorespiratory parameters in the awake pigeon and during anaesthesia with isoflurane. (January 2016) - Botman, Julie; Dugdale, Alex; Gabriel, Fabien; Vandeweerd, Jean-Michel
Abstract: Objective: To determine baseline cardiovascular and respiratory variables in the awake pigeon, and to assess those variables during anaesthesia at the individual minimal anaesthetic concentration (MAC) of isoflurane during spontaneous breathing. Study design: Prospective, experimental trial. Animals: Seven healthy adult pigeons weighing a mean ± standard deviation (SD) of 438 ± 38 g. Methods: Heart rate (HR), heart rhythm, respiratory rate ( f R ), end-expired carbon dioxide tension (Pe 'CO2 ), indirect systolic arterial pressure (SAP) and cloacal temperature (T) were measured in birds in the awake state (after acclimatization to handling). Two weeks later, the pigeons were anaesthetized with isoflurane in order to determine their MAC and evaluate the same cardiovascular and respiratory variables during a further 40 minutes of isoflurane anaesthesia. Results: In the awake pigeon, mean ± SD HR, SAP, f R, Pe 'CO2 and T were, respectively, 155 ± 28 beats minute −1, 155 ± 21 mmHg, 34 ± 6 breaths minute −1, 38 ± 8 mmHg (5.1 ± 1.1 kPa) and 41.8 ± 0.5 °C. Mean isoflurane MAC was 1.8 ± 0.4%. During maintenance of anaesthesia at MAC, although no significant decreases between values obtained in the awake and anaesthetized states emerged in HR or respiratory rate, significant decreases in SAP and cloacal temperature and an increase in Pe 'CO2 were observed. No arrhythmia was identified in awake pigeons, whereas second- and third-degree atrioventricular blocks occurred under isoflurane. Conclusions and clinical relevance: Isoflurane MAC in pigeons appeared to be higher than in other avian species. Isoflurane anaesthesia in pigeons resulted in hypercapnia, hypotension, mild hypothermia and second- and third-degree atrioventricular blocks.